3-T high-b-value diffusion-weighted MR imaging of hyperacute ischemic stroke in the vertebrobasilar territory = Imagerie de diffusion en IRM 3T à b élevé dans l’accident ischémique hyperaigu du territoire vertébobasilaire - Lettau, Michael; Laible, Mona (Journal of neuroradiology, 2012)
Background and purpose: Diffusion-weighted imaging (DWI) is the key method for diagnosing acute ischemic stroke. Applied b values in stroke diffusion studies are usually in the range of 800–1500 s/mm2, but progress in magnetic resonance (MR) technology now permits higher b values. However, it is uncertain whether high-b-value DW sequences improve the detection of acute and hyperacute ischemic lesions. The aim of this study is to explore the sensitivity of high b values vs standard b values at 3 T in hyperacute stroke in the vertebrobasilar territory. Material and methods: 3-T DWI was performed in referred patients with a clinical diagnosis of hyperacute (< 6 h from onset) cerebral infarction using conventional MR sequences as well as DW sequences. Examinations included the usual DW sequence (b = 1000 s/mm2) and two high-b-value DW sequences (b = 3000 s/mm2 and b = 5000 s/mm2). Patients with hyperacute stroke in the posterior circulation were included if MR imaging, including the usual DW sequence, was normal or if the diagnosis was uncertain.Results: In all six studied patients, ischemic lesions were better visualized with high-b-value DWI compared with the usual DWI. On increasing the b value, DW images appeared to be noisier while white-matter tracts became progressively hyperintense. Conclusion: At 3 T, high-b-value DW sequences may be helpful for diagnosing hyperacute infarctions in the vertebrobasilar territory, but further studies are needed to confirm this hypothesis.
Available online 16 December 2011
Gesehen am 23.08.2018